Evaluasi Kurikulum Aqidah Akhlak di Madrasah Ibtidaiyah: Menyelaraskan Pendekatan Tematik dan Metode Pengajaran dengan Penggunaan ICT: Evaluation of the Aqidah Akhlak Curriculum in Madrasah Ibtidaiyah: Aligning Thematic Approaches and Teaching Methods with ICT Utilization - Karlaely, Irma (Perkumpulan Peneliti dan Pegiat Literasi, 2023)
This study evaluates the Aqidah Akhlak curriculum at Madrasah Ibtidaiyah, focusing on the appropriateness of approaches, strategies, and teaching methods. Although adapted to curriculum development principles, the curriculum remains a human creation that falls short of divine perfection. The primary focus is on the Aqidah Akhlak subjects for grades I and III, employing a thematic approach to facilitate understanding and memorization in line with competency standards. A deeper evaluation is necessary, particularly regarding the suitability of approaches and methods to the material characteristics, student and teacher abilities, and the availability of information and communication technology (ICT). The study reveals that curriculum evaluation and the application of Aqidah Akhlak learning at Madrasah Ibtidaiyah tend to be formative and summative, using written and oral tests focusing on cognitive aspects. The implementation of action tests encompassing psychomotor and cognitive aspects remains limited, while non-test evaluation methods such as sociometry and anecdotal records are infrequent. Highlighting a new theory in evaluating Aqidah Akhlak subjects at Madrasah Ibtidaiyah, this research underscores the importance of assessing student performance as a preferred alternative.